Comparison Study Between Airfoil to Enhancement the Wind Turbine Power - BARIR Djihad; KHALIL Chourouk (University of Shahid Hama Lakhdar - El Oued, 2025)
"Abstract: The increasing demand for sustainable energy has heightened the need for efficient and cost-effective renewable energy systems. Among these, small-scale wind turbines offer a practical solution for decentralized energy generation, particularly in rural, agricultural, and residential settings. This thesis presents the aerodynamic design, optimization, and performance analysis of a 3-kW horizontal-axis wind turbine blade using four different airfoils: NACA 6409, NACA 4412, S818, and Eppler 387. The study begins with a comparative analysis of the selected airfoils using XFOIL to evaluate key aerodynamic parameters, including lift and drag coefficients and the lift-to-drag ratio. The NACA 6409 airfoil give the highest performance, at an angle of attack of 6°, indicating its potential for maximizing energy extraction.The blade geometry was then designed and optimized using QBlade software, which incorporates Blade Element Momentum (BEM) theory and is integrated with XFOIL for precise airfoil modeling. Simulations were conducted to evaluate the power coefficient and output power across a range of tip speed ratios (TSR). Results showed that the NACA 6409-based blade achieved the highest power coefficient of 0.52 and a maximum power output of 3,200 W at a TSR of 7, outperforming the other airfoils " "الملخص: أدى الطلب المتزايد على الطاقة المستدامة إلى ازدياد الحاجة إلى أنظمة طاقة متجددة فعّالة ومنخفضة التكلفة. ومن بين هذه الأنظمة، تُقدّم توربينات الرياح صغيرة الحجم حلاً عمليًا لتوليد الطاقة اللامركزية، لا سيما في المناطق الريفية والزراعية والسكنية. تُقدّم هذه الأطروحة التصميم الديناميكي الهوائي، والتحسين، وتحليل الأداء لشفرة توربين رياح أفقي المحور بقدرة 3 كيلوواط، باستخدام أربعة أجنحة هوائية مختلفة: NACA 6409 ، وNACA 4412، وS818، وEppler 387. تبدأ الدراسة بتحليل مقارن للأجنحة الهوائية المختارة باستخدام تقنية XFOIL لتقييم المعايير الديناميكية الهوائية الرئيسية، بما في ذلك معاملات الرفع والسحب ونسبة الرفع إلى السحب. يُقدّم جناح NACA 6409 أعلى أداء، بزاوية هجوم تبلغ 6 درجات، مما يُشير إلى قدرته على تعظيم استخراج الطاقة. تم بعد ذلك تصميم وتحسين هندسة الشفرة باستخدام برنامج QBlade، الذي يدمج نظرية زخم عنصر الشفرة (BEM)، ويُدمج مع XFOIL لنمذجة دقيقة للجناح. أُجريت عمليات محاكاة لتقييم معامل القدرة وقوة الخرج عبر مجموعة من نسب سرعة الطرف (TSR). أظهرت النتائج أن الشفرة القائمة على NACA 6409 حققت أعلى معامل قدرة (0.52) وأقصى قدرة خرج (3200 واط) عند نسبة سرعة طرفية (TSR) قدرها 7، متفوقةً بذلك على الأجنحة الأخرى. "
Master's thesis in electromechanics.2025
Keywords: 1. Airfoils 2. Wind turbines 3. Mechanical power enhancement 4. Turbine efficiency 5. Aerodynamics 6. Comparative study; 1. الجنيحات الهوائية 2. عنفات الرياح 3. تحسين القدرة الميكانيكية 4. كفاءة التوربينات 5. الديناميكا الهوائية 6. دراسة مقارنة